Peran Peran Change Management Untuk Meningkatkan Kinerja Organisasi Kantor Pelayanan Pajak Madya Malang - Edwin Agus Buniarto (Yayasan Literasi Sains Indonesia, 2023)
Organizational performance is a level of organizational success during a certain period in carrying out tasks in order to achieve goals. Organizations and society have a reciprocal relationship so that all changes that occur in society will ultimately require the organization to make changes. Change Management at the Malang Madya Tax Service Office requires proper management so that service objectives, tax revenues and organizational performance can be achieved. The steps of the Malang Madya Tax Service Office in planning Change Management management policies by launching various programs include forming change agents, establishing performance managers, managing risk management and carrying out monitoring and evaluation activities on the implementation of Change Management so as to be able to encourage employees to improve organizational performance to achieve common goals. With the Change Management management program at the Malang Madya Tax Service Office, it can improve employee performance and organizational performance to achieve organizational goals so that in 2021, the Malang Madya Tax Service Office succeeded in obtaining an Organizational Performance Score (NKO) of 108.05%. With proper change management, it can encourage the performance of all employees so as to improve organizational performance to achieve organizational goals. The same thing can be used as an example for other agencies in managing Change Management so that organizational performance can be improved to be even better than before.